The Analysis Between Purchasing Power Parity and Exchange Rates, Inflation and Gross Domestic Product in Developing and Developed Countries Asia and Europe During Covid-19 Pandemic - Adistya, Pragita Aci; Radise, Sidha Belanandra; Agustin, Grisvia (IJBLE Scientific Publications Community Inc., 2024)
The study aims to analyze Purchasing Power Parity (PPP) and exchange rates, inflation and Gross Domestic Product (GDP) in developing and developed countries in Asia and Europe during the covid-19 pandemic. The data used secondary data, obtained from the websites of the Central Bank of Indonesia, World Bank, International Monetary Fund (IMF) and Organization for Economic Cooperation and Development (OECD) from 2003 to 2020. This research used method of Vector Error Correction Model (VECM). The results show that the GDP, inflation and exchange rate variables have positive and negative responses to changes in PPP values during the observation period, especially during the Covid-19 pandemic. This condition can occur because the economy in each country experiences fluctuations, especially during the Covid-19 pandemic. This has an impact on the PPP value in these 10 countries, which causes each country to take financial and monetary policies in accordance with the problems they face